The land tenure and the land use among supiori in Papua - Simon Abdi K. Frank; Agustinus Wenehen; Usman Idris (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2020)
This article aims to explore various forms of land tenure and land use in Sorendiweri Village in East Supiori District, Papua Province. This research uses descriptive research using ethnography. The technique of determining informants is done purposively by determining key informants first that guides researchers to search for further informants. Data collection techniques used are in-depth interviews and FGD (Focus Group Discussion). Data analysis was carried out based on the factual culture of the community. The results show that the pattern of land tenure in the local population is communal at the clan level. Then, according to the local population, psychomo-logical and historicize view of customary land is very dominant because it states that customary land tenure in popular clans such as Sauyas that is more in line with history and relationships between clans. In addition, land tenure conflicts often occur because of the spread of land clearing in customary rights for infrastructure development and etc.